2020
DOI: 10.21532/apfjournal.v5i1.133
|View full text |Cite
|
Sign up to set email alerts
|

Does Moral Hazard Occour in the Implementation of Social Health Insurance? Evidence From Public Hospitals in a Rural Province of Indonesia

Abstract: Indonesia is now encountering moral hazard problems in the implementation of social health insurance. BPJS, as the administrator of Indonesia’s National Health Insurance, reported that there was an increase in deficit in the 4 years of the implementation of National Health Insurance from US$ 228 million in 2014 to US$ 470 million in 2016. Despite efforts conducted to overcome the problem, no evidence-based predictor that might be significantly associated with moral hazard in a rural province hospital in Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…The percentage of readmission is 37.9%. This result is greater than the Niu et al (2013) study results, which only stated that almost 20% of readmissions occurred in Medicare patients (Machmud et al, 2020). The percentage of keystroke mistakes is 7.1%.…”
Section: Fraud In Healthcare Facilitiescontrasting
confidence: 60%
See 2 more Smart Citations
“…The percentage of readmission is 37.9%. This result is greater than the Niu et al (2013) study results, which only stated that almost 20% of readmissions occurred in Medicare patients (Machmud et al, 2020). The percentage of keystroke mistakes is 7.1%.…”
Section: Fraud In Healthcare Facilitiescontrasting
confidence: 60%
“…Fraud in health care facilities can occur due to several things, including incomplete medical record files (Yuniati, 2017;Zafirah et al, 2017;Zafirah et al, 2018;Bastani et al, 2019;Suryandari, 2019;Kusumawati & Pujiyanto, 2020;Machmud et al, 2020). Then, doctors' writings that are difficult to read also make it difficult for a coder to code for a disease (Yuniati, 2017;Kusumawati & Pujiyanto, 2020;Syafrawati et al, 2020;Taslim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the longer care system is also a burden on patients and has the potential to become fraud in the health sector. (Machmud et al 2020) The study found that the appointment of non-medical doctors as internal veri ers, lack of clarity in guidelines for doctors and coding, and poor coordination between hospitals and health insurance are the causes of upcoding in the hospital (Syafrawati et al, 2020).…”
Section: B Impact Of Corruptionmentioning
confidence: 99%
“…EducationApart from the above factors, there has also been a delay in receiving health care, including slow processing times and gaps in the number of claims and the amount paid(Panda et al, 2016).Indonesia is now facing several problems in implementing BPJS health insurance because it has experienced a de cit from 2014-2018(Machmud et al, 2020) …”
mentioning
confidence: 99%